'Bring Your Own Device': Considering potential risks to student health. (June 2016) - Merga, Margaret K
Background and context: Schools in Australia and internationally are increasingly adopting a Bring Your Own Device (BYOD) approach to teaching and learning. The review: While discussion of a BYOD approach has taken place, there is a dearth of consideration of the potential impact of BYOD policy on student health. Implementation of a BYOD policy may have implications for increased sedentary behaviour, as well as spinal and postural health. Increased use of devices at home to complete homework may also have implications for sleep duration, which in turn may impact upon a range of physical and cognitive issues. BYOD implementation may also increase student vulnerability to cyberbullying. These and other health issues are discussed. Recommendations: Schools may find it helpful to adopt a risk analysis approach informed by social cognitive theory, with an emphasis on the provision of knowledge and the fostering of self-efficacy in order to safeguard against potential health risks. As this issue has significance for researchers in both health promotion and education, an interdisciplinary approach should be taken.